Studies on the radiation sensitivity of chromatin from cultured cells - Nackerdien, Zeena E.(Zeena Elnisa) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.